PENGENDALIAN BAHAN BAKU (PVC) GUNA MENEKAN BIAYA PRODUKSI PADA HONG BROTHERS INDUSTRI PLASTIK DENGAN METODE ECONOMIC ORDER QUANTITY - Iskandar Ali Alam; Yulianto Yulianto; Hengky Achmad Subing (Jurnal Manajemen dan Bisnis, 2022)
Supply of materials is an important asset for a company which do  production process activities. If the supply of materials is optimal, it will support the smooth running of the company's production process. Supply of material’s planning and control systems are needed. The research is a quantitative study, which is to the detail review tp the use of the Economic Order Quantity (EOQ) method for controlling the supply of materials in the Hong Brothers Plastic Industry. The research’s object is the amount of purchases, the amount of inventory, the amount of supply material used for production process activities, and the ordering costs and storage costs of the supply of materials. The results of study found an optimal supply of PVC materials used the EOQ method is 2732 kg with Purchase Frequency is 8 times, Safety Stock is 898 kg and ROP is 1070 kg with TIC is Rp 7,562,567. Meanwhile, paint materials used the EOQ method is 527 kg with Purchase Frequency is 8 times, Safety Stock is 105.4 kg and ROP is 139 kg with TIC is Rp 7,562,169. Then for Thinner used the EOQ method is 2565 liters with Purchase Frequency is 8 times, Safety Stock is 501 liters and ROP of 663 kg with TIC is Rp 7,562,486.